GeoHazardView: Interactive presentation of geological hazard maps - Wakita, K.; Kato, H.; Bandibas, J. (Geologija, 2003)
This paper presents an interactive method of showing geological hazard maps and other related information using the software developed at the Geological Survey of Japan. The main purpose of the software is to easily provide information about geological hazards. In this paper, the region of interest is East Asia. The software provides a good alternative to viewing geological hazard maps and other related information in paper form. It incorporates spatial and a-spatial data to interactively present the time, locations and extent of occurrence of geological hazards and other related information. Queries for a particular hazard information like number of casualties, magnitude and location of earthquake epicenters, names and locations of volcanoes erupted in a particular year can be easily done. Simulations of the occurrence of a particular geological event like the spread of volcanic ash during major volcanic eruptions can also be shown. The new software is named GeoHazardView.